Aplikasi Penjualan di Toko Emas Surya Kencana Kota Bitung Menggunakan Framework Codeigniter - Baharuddin Mustahir; Olivia Kembuan; Sondy Kumajas (JOINTER : Journal of Informatics Engineering, 2021)
Abstract— This Surya Kencana Gold Shop is a shop that is engaged in buying and selling gold jewelry that has a specific business character. This study aims to design and implement a WEB-based sales application at the Surya Kencana Gold store. The method used in developing this application is Waterfall where there are six stages, namely Analysis, Design, Coding, Testing, and Implementation of Maintenance Programs, used with the framework are codeigniter. The results of the research are a WEB-based Gold Shop sales application and have service functions, namely the function of purchasing, storing, selling and selling reports so that they can improve the sales system for the better. The method that used of testing this system is Blackbox texting method.